Geometric Pattern of Proximal Landing Zones for Thoracic Endovascular Aortic Repair in the Bovine Arch Variant. (May 2020) - Marrocco-Trischitta, Massimiliano M.; Alaidroos, Moad; Romarowski, Rodrigo M.; Secchi, Francesco; Righini, Paolo; Glauber, Mattia; Nano, Giovanni
Abstract : Objective: The aim was to investigate whether the "bovine" aortic arch (i.e. arch variant with a common origin of the innominate and left carotid artery (CILCA)) is associated with a consistent geometric configuration of proximal landing zones for thoracic endovascular aortic repair (TEVAR). Methods: Anonymised thoracic computed tomography (CT) scans of healthy aortas were reviewed to retrieve 100 cases of CILCA. Suitable cases were stratified according to type 1 and 2 CILCA, and also based on type of arch (I, II, and III). Further processing allowed calculation of angulation and tortuosity of the proximal landing zones. Centre lumen line lengths of each proximal landing zone were measured in a view perpendicular to the centre line. All geometric features were compared with those measured in healthy patients with a standard arch configuration ( n = 60). Two senior authors independently evaluated the CT scans, and intra- and interobserver repeatability were assessed. Results: The 100 selected patients (63% male) were 71.4 ± 7.7 years old. Type 1 CILCA (62/100) was more prevalent than type 2 CILCA (38/100), and the two groups were comparable in age ( p = .11). Zone 3 presented a severe angulation (i.e . > 60°), which was greater than in Zone 2 ( p < .001), and a consistently greater tortuosity than Zone 2 ( p = .003). This pattern did not differ between type 1 and type 2 CILCA. A greater tortuosity was also observed in Zone 0, which was related to increased elongation of the ascending aorta ( i.e. Zone 0), than the standard configuration. The CILCA had an overall greater elongation, and Zone 2 also was specifically longer. When stratifying by type of arch, reversely from Type III to Type I, the CILCA presented a gradual flattening of its transverse tract, which entailed a consistent progressive elongation ( p = .03) and kinking of the ascending aorta, with a significant increase of Zone 0 angulation to even a severe degree ( p = .001). Also, from Type III to Type I, Zone 2 presented a progressively shorter length ( p = .004), which was associated with increased tortuosity ( p < .05). Mean intra- and interobserver differences for angulation measurements were 1.4° ± 6.8° ( p = .17) and 2.0° ± 10.1° ( p = .19), respectively. Conclusion: CILCA presents a consistent and peculiar geometric pattern compared with standard arch configuration, which provides relevant information for TEVAR planning, and may have prognostic implications.